Restoration of Primary Anterior Teeth with Glass Fiber-Reinforced Post and Core: 3-Year Follow-Up Case Report - Salah Afraa; Hashim Raghad; Khalid Ayam; Hamid Aeshah (Case Reports in Dentistry)
Background. Esthetic appearance of primary anterior teeth is one of the major demands in the dental field. Destructed anterior primary teeth due to caries is considered a major issue due to the difficulty in regaining the esthetic crowns and attaching them until the normal exfoliation time. There have been many attempts and tools used to attach the composite crowns to the treated canals of primary anterior teeth. The study evaluates endodontic treatment for destructed primary maxillary incisors with a glass fiber-reinforced post as a retentive tool to hold the esthetic composite crowns until the normal exfoliation time of primary incisors. Case Presentation. A four-year-old child attending a dental clinic complained of pain of maxillary incisors. Dental examination showed irreversible pulpitis of four maxillary incisors indicated for root canal treatment and crown placement. Endodontic treatment was carried out, and a glass fiber-reinforced post was used to get successful retention for the composite crowns. Follow-up was carried out for 3 years. The 3 crowns were retained successfully until replaced by permanent incisors. One crown fell during the treatment course. Conclusion. Retention of primary teeth is one of the challenges in pediatric dentistry. Restoration of primary decayed incisors is important for child medical, physical, and psychological conditions. A glass fiber-reinforced post and core is a strong retentive tool for composite crown retention for primary incisors. This procedure opens the door for a strong tool to retain composite crowns for a long time. The glass fiber-reinforced post and core is a strong retentive tool for composite crown retention for primary incisors.